A Customization Grammar: Describing the customization process of apartment design. (September 2017) - Griz, Cristiana; Amorim, Luiz; Mendes, Leticia; Holanda, Maria Augusta; Carvalho, Thais
This article introduces the concept of Customization Grammar, an analytical shape grammar that describes the alterations introduced by homeowners to high-standard apartments before occupation. This is viewed as a contemporary phenomenon that reveals the incompatibility between social demands and housing units offered by the current real estate market in Recife, Brazil. It is expected that the proposed grammar could support mass customization design procedures and able to generate suitable housing units to current and future lifestyles.